(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
The principle of free competition, studied and developed by the academic discipline of competition law, has a clear multidisciplinary nuance, to which judges are not usually very attentive, given the typically positivist characteristics of our training. However, the sources of law are undergoing a transformation, mainly due to the appreciation of jurisprudential precedents. Respect for what has already been decided is the main characteristic of modern English law, the Common Law, the study of which has become a requirement of the new Code of Civil Procedure, which requires courts to maintain their case law uniform, stable, complete and coherent (art. 926). In this study, carried out in the context of comparative law, we seek to identify how the perception of the Judiciary as a positive source of law is evolving, notably by respecting decisions made in previous cases. Going through issues such as the formation of judicial decisions and the independence of judges, we present the challenge posed not only to Brazilian magistrates of using a tool from another system, but also to English judges. While we will have elements of Common Law, they need to apply decisions made in the Civil Law environment, due to their country’s participation in the European Union. Competition law offers a suitable environment for us to demonstrate how to receive the influence of other legal systems, changing the way we operate (in this case, through different procedural postures), which can bring new inspiration for the solution of concrete cases.